Analysis of Leading Sectors and Characteristics of Provincial Economic Growth in Indonesia: Analysis of Leading Sectors and Characteristics of Provincial Economic Growth in Indonesia - Khusnudin Tri Subhi; Azka Al Azkiya (Jurnal Forum Analisis Statistik, 2022)
Gross Domestic Product or GDP is one indicator of a country's economy moving the economic sector. The Covid-19 pandemic caused the economy of Indonesia in the second quarter of 2020 compared to the second quarter of 2019 (YoY) to experience a 5.32 percent contraction. In increasing the economic growth rate, adjusting it to each region's potential is necessary, which is the leading sector. This study aims to analyze the basic or leading sectors and the economic growth conditions of the provinces in Indonesia and group the provinces based on their proximity characteristics. The method used is the Ward and Location Quotient using secondary data from Statistics Indonesia. The results show that 25 provinces in Indonesia have an agricultural base sector. The mining sector is primarily concentrated in eastern Indonesia and tends not to affect the Covid-19 because it can grow fast. Provinces with a manufacturing industrial base sector are focused on Java. The clustering results formed 5 clusters, each province having similar characteristics. The growing cluster is a province with a mining base sector. The sector with intense contraction is a province that provides accommodation, food, and drink. Local governments can restore the economy starting from the base sector.